2020
DOI: 10.1007/s10854-020-03367-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and shear strength properties of RHA-reinforced Sn–0.7Cu composite solder joints on bare Cu and ENIAg surface finish

Abstract: In this study, the joint effect of rice husk ash (RHA) reinforcement as an alternative silica source and electroless nickel immersion silver (ENIAg) surface finish on the intermetallic compound (IMC) formation and shear strength of the Sn-0.7Cu solder system was investigated. A series of plain and composite lead-free solder systems (Sn-0.7Cu−xRHA; x = 0, 0.01, 0.05 and 0.1 wt%) was successfully developed and subjected to reflow soldering on bare Cu and ENIAg surface finish. After conducting a comprehensive mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It can be deduced from the decrease in the shear strength of composite solders that the nanoparticles (rice husk ash) added to the solders were unable to strengthen the solder due to non-uniform particle dispersion and thus, dropped the solder deformation resistance by allowing the movement of dislocation and pin grain boundaries in the solder matrix, Figure 5. This can be further rationalized by a study where the introduction of rice husk ash to the solder joint promoted the formation and localization of intermetallic compound clusters close to the solder/ substrate interface [30]. Solder joint fracture through the interface when the applied stress is less than the solder strength and the interfacial strength is higher than the interfacial bonding strength.…”
Section: Shear Strength Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be deduced from the decrease in the shear strength of composite solders that the nanoparticles (rice husk ash) added to the solders were unable to strengthen the solder due to non-uniform particle dispersion and thus, dropped the solder deformation resistance by allowing the movement of dislocation and pin grain boundaries in the solder matrix, Figure 5. This can be further rationalized by a study where the introduction of rice husk ash to the solder joint promoted the formation and localization of intermetallic compound clusters close to the solder/ substrate interface [30]. Solder joint fracture through the interface when the applied stress is less than the solder strength and the interfacial strength is higher than the interfacial bonding strength.…”
Section: Shear Strength Testmentioning
confidence: 99%
“…Solder joint fracture through the interface when the applied stress is less than the solder strength and the interfacial strength is higher than the interfacial bonding strength. Hence, the deterioration of the composite solder joints increased with rising rice husk ash addition [30]. More so, the added rice husk ash has the possibility of not entirely dispersing in the solder after soldering.…”
Section: Shear Strength Testmentioning
confidence: 99%
“…Teoh et al [20] reported that the mechanical strength of Sn-0.7Cu improved by adding Bi into the solder alloy. Hanim et al [21] reported that the electroless nickel immersion silver (ENIAg) surface finish significantly enhanced the shear strength of the solder joint, as it provided a more stable metallurgical bond of the solder joint. Despite the abovementioned studies and others involving the improvement of the performance of Sn-0.7Cu, studies on the modification of the substrate used in the soldering process remain limited.…”
Section: Introductionmentioning
confidence: 99%